The Milan System for Reporting Salivary Gland Cytopathology (Springer International Publishing, 2018)
This volume describes a uniform international approach for classifying and reporting salivary gland FNA samples. The new reporting system is evidence-based using data from the literature as well as upon the experience of a multi-disciplinary group of leading experts involved in the field of salivary gland cytopathology. Each diagnostic category of this novel salivary gland reporting system includes detailed descriptions of the cytologic criteria as well as a comprehensive set of photomicrographs demonstrating all of the key microscopic features along with annotated descriptions for each image. Designed as a practical book with easy readability, The Milan System for Reporting Salivary Gland Cytopathology combines the high-quality images of an atlas with a logical approach described in concise text-form and in line-drawing algorithms. It presents for the first time, an international cytologic reporting system for salivary gland lesions designed and endorsed by a panel of experts in the field.